Partnership Research with Indigenous Communities: Fostering Community Engagement and Relational Accountability - Jennifer Brant; Shelley Stagg Peterson; Nicola Friedrich (Brock University, 2023)
Drawing from principles of ethical research we derived from our review of national and international policy documents, in this paper we reflect on our research experiences working in partnership with Indigenous educators in a project to support young Indigenous children's oral and written language development through collaborative action research. Then, acting on lessons learned from this first partnership project, we describe our efforts to attend to these ethical research principles in a second partnership project to support Indigenous children's writing and Indigenous language and cultural learning through teacher-initiated, culturally specific, play-based activities. We offer our reflections as a starting point for conversations about ethical and relational responsibilities of doing partnership research with and for Indigenous communities.